Intraretinal hemorrhages in newborns: Incidence and associated factors (2016)
Purpose: To determine the incidence of intraretinal hemorrhage in newborns at the Hospital de San José, Bogotá, Colombia from September 2009 to September 2010. Design: Cohort study. Methodology: Live newborns were examined at the San José Hospital for a year (September 2009 to 2010), analyzing neonatal and maternal factors associated with the presence of intraretinal hemorrhages. A simple random cluster sampling was used, excluding newborns with a compromised general status, as well as those whose parents or legal guardians did not sign the informed consent form. Patients with the presence of intraretinal hemorrhages were examined every 2 weeks until resolution was observed. Results: A total of 190 newborns were examined, finding an incidence of intraretinal hemorrhages of 22.6% (95% CI 16.6 to 28.6). Most of the mothers were nulliparous (55.8%) and deliveries were eutocic (65.1%). From newborns with hemorrhages, 81.3% were born at term, and hemorrhages in most patients (93.0%) were resolved by the second week of monitoring. Associations between hemorrhages and cesarean section (RR 0.42, CI 0.22 to 0.79) and episiotomy (RR 1.73, CI 1.02 to 2.94) were observed. Conclusions: Newborns who presented intraretinal hemorrhages were children of nulliparous mothers on whom episiotomy was performed, and some with eutocic and instrumenteddeliveries. The first two variables had statistical significance for the development of intraretinal hemorrhages.